Fiscal Decentralization, Institutions, and Politics: Determinants of Road Quality in Indonesia - Cahyaningrum, Adhilia Mega; Sarjiyanto, Sarjiyanto; Samudro, Bhimo Rizky (Fakultas Ekonomi dan Bisnis Universitas Lampung, 2025)
Roads are strategic infrastructure that support connectivity and regional development. The deterioration of road quality can hinder mobility and suppress economic activity. This study analyzes the factors affecting road quality, particularly those related to road damage, by emphasizing the role of the Special Allocation Fund (DAK), institutional quality measured through the democracy index and corruption cases, and political competition. A quantitative approach using panel data regression was applied to 33 provinces in Indonesia over the 2021–2023 period. The visualization results reveal disparities in road quality between Java and non-Java regions. Statistical tests show that DAK and institutional quality do not have a significant effect on road quality. Conversely, political competition has a significant effect, indicating that healthy political competition promotes accountability and efficiency in infrastructure management. The study also finds that the control variables—vehicle volume and per capita income—have a positive and significant relationship with the ratio of damaged roads. The implications of this study highlight the need to improve Indonesia’s road infrastructure quality by strengthening political competition and enhancing budget governance.